Women, gender, and technology - Fox, Mary Frank; Johnson, Deborah G., 1945-; Rosser, Sue Vilhauer (Women, gender, and technology., 2006)
Looking into the co-creation of gender and technology, this work explores how gender and technology work in particular domains, including film narratives, reproductive technologies, information technology and the profession of engineering.